2002
DOI: 10.2320/matertrans.43.2201
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical Properties of Nb-18Si-5Mo-5Hf-2C <I>In-Situ</I> Composite Prepared by Arc-Casting Method

Abstract: Niobium-base in-situ composite, Nb-18Si-5Mo-5Hf-2C (in mol%), was fabricated by arc-casting method and heat-treated at 2070 K for 20 h in vacuum. The microstructure is composed of Nb solid solution (Nb SS ) matrix phase and secondary phase of Nb 5 Si 3 . The Nb 5 Si 3 was found to have two kinds of structure: one is the α phase reported in the Nb-Si binary phase diagram and the other is a hexagonal phase with Mn 5 Si 3 -type structure. To evaluate the mechanical properties of the composite, nano-indentation ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 27 publications
(13 citation statements)
references
References 9 publications
0
13
0
Order By: Relevance
“…The refractory Nb-Si-based alloys with high melting temperatures are of interest as candidate materials for aero-engine applications. [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15] The microstructure of the Nb-Si-based alloys consists of hard and brittle intermetallic Nb 5 Si 3 and relatively ductile Nb-solid solution (Nb ss ) phases. The Nb 5 Si 3 exhibits excellent high-temperature strength retention and creep resistance, [1] but poor ductility and fracture toughness.…”
Section: Introductionmentioning
confidence: 99%
“…The refractory Nb-Si-based alloys with high melting temperatures are of interest as candidate materials for aero-engine applications. [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15] The microstructure of the Nb-Si-based alloys consists of hard and brittle intermetallic Nb 5 Si 3 and relatively ductile Nb-solid solution (Nb ss ) phases. The Nb 5 Si 3 exhibits excellent high-temperature strength retention and creep resistance, [1] but poor ductility and fracture toughness.…”
Section: Introductionmentioning
confidence: 99%
“…The estimated elastic modulus in the present study is in good agreement with reported values, which were evaluated for both phases in SMHC18 with an applied load of 9.81 mN in the previous report. 9) Considering that the elastic modulus shows almost no dependence upon the applied load in the nanoindentation tests, E obtained from formula (3) could be regarded as reasonable. The estimated elastic modulus of the Nb 5 Si 3 phase is somewhat greater than that (E % 326 GPa) of monolithic Nb 5 Si 3 fabricated by the powder metallurgy method (P/M).…”
Section: Evaluation Of the Mechanical Properties Of Nb Ss Andmentioning
confidence: 99%
“…In this decade, significant progress has been achieved in understanding the mechanical behavior of Nb-base in-situ composites, such as their high temperature compression properties, 6,7) high temperature tensile properties 8,9) and room temperature fracture toughness. 10) However, there are only a few reports available on the hardness, H, and elastic modulus, E, of the constituent phases of Nb SS /Nb 5 Si 3 in-situ composites, despite of the importance of the property for material design, especially for fracture toughness improvement.…”
Section: Introductionmentioning
confidence: 99%
“…Like the harmful r phase in Ni-base superalloys, martensitic stainless steels, and many other heat-resistant high alloying steels, the single-phase Cr 13 Ni 5 Si 2 is also so brittle that it has little significance for practical applications as a bulk wear-resistant material. It is demonstrated that one of the most effective methods to enhance the toughness and ductility for many intermetallic alloys is the in-situ incorporation of a ductile second phase [14][15][16][17][18] via multicomponent alloying. The Ni-base solid solution (c) is well known for its excellent combination of ductility, toughness, oxidation resistance, high-temperature strength, and corrosion resistance when dissolved with high contents of Cr and Si.…”
Section: Introductionmentioning
confidence: 99%